2018
DOI: 10.2110/jsr.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Acid-saline-lake Systems of the Triassic Mercia Mudstone Group, County Antrim, Northern Ireland

Abstract: The Triassic Mercia Mudstone Group of County Antrim, Northern Ireland, is dominated by red beds and evaporites. After only limited study, both marine and continental environments have been proposed previously. Here, we describe these rocks for the first time from core and petrographic observations to interpret depositional environments and conditions, such as water depth, salinity, and aridity. Bedded halite, bedded gypsum, displacive halite, and red siliciclastic mudstone lithologies comprise most (~80%) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Ephemeral acid saline lakes have been documented in Western Australia (e.g., Mann 1988;McArthur et al 1991;Alpers et al 1992;Benison et al 2007;Bowen and Benison 2009) and northwestern Victoria (e.g., Alpers et al 1992;Long et al 1992aLong et al , 1992bMacumber 1992). Permian and Triassic acid saline lake deposits in the U.S. midcontinent and Northern Ireland have also been identified (Benison et al 1998;Benison and Goldstein 2000;Andeskie et al 2018). Although similar in water chemistry and mineral assemblage to modern Australian and Permo-Triassic acid saline environments, salars Gorbea and Ignorado have a different geological setting and a different set of sedimentary processes and products than any acid brine environments previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ephemeral acid saline lakes have been documented in Western Australia (e.g., Mann 1988;McArthur et al 1991;Alpers et al 1992;Benison et al 2007;Bowen and Benison 2009) and northwestern Victoria (e.g., Alpers et al 1992;Long et al 1992aLong et al , 1992bMacumber 1992). Permian and Triassic acid saline lake deposits in the U.S. midcontinent and Northern Ireland have also been identified (Benison et al 1998;Benison and Goldstein 2000;Andeskie et al 2018). Although similar in water chemistry and mineral assemblage to modern Australian and Permo-Triassic acid saline environments, salars Gorbea and Ignorado have a different geological setting and a different set of sedimentary processes and products than any acid brine environments previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…The geochemistry of mudstones within the MMG succession has also been discussed, with some favouring marine or marine derived fluids as the source of Mg in the clay minerals and carbonates (Taylor, ; Leslie et al ., ; Leslie & Tucker, ), whereas others have favoured continentally evolved fluids as the source (Wright & Sandler, ). The most recent investigation, of a halite‐dominated succession in Northern Ireland (Andeskie et al ., ), attributes deposition entirely to continental processes, with evaporation, aeolian process and periodic flooding created acid–saline lakes, mudflats and desert palaeosols.…”
Section: Discussion: Dryland Mudstone Facies Developmentmentioning
confidence: 99%
“…The relative importance of mixed continental/marine fluids and continentally evolved brines for dolomitization are difficult to assess in the absence of geochemical data. However, this study has found no direct evidence, such as marine biota, tidal features or significant stratigraphic breaks (Andeskie et al ., ), to indicate significant marine influence in the MMG successions of the Severn and Bristol Channel basins. Instead the presence of widespread pedogenic features within alluvial, aeolian and playa‐lacustrine facies is consistent with deposition in a non‐marine, continental setting.…”
Section: Discussion: Dryland Mudstone Facies Developmentmentioning
confidence: 99%
See 2 more Smart Citations